Penerapan Metode MOORA dan Pembobotan ROC Dalam Pemilihan Alat KB - Teddy Erlambang Teddy; Muhammad Luthfi Akbar; Nola Dita Puspa; Mesran (Journal of Computing and Informatics Research, 2023)
Family Planning (KB) is a family implementation to determine the number of births. The important thing in the success of this implementation is the use of contraceptives. Contraceptives are determined based on the effect on contraceptive users. The main factor of the problem is the absence of suitable contraception for all users. With these problems a Decision Support System (DSS) is needed to determine the appropriate contraceptive method for the user's condition. In selecting decisions using the Multi-Objective Optimization by Ratio Analysis (MOORA) method. The MOORA method is used because this method can determine decisions based on criteria in the level of efficiency and the selection process is accurate but has simplicity. The criteria needed at this selection stage are price, age, menstrual history, effectiveness, time period, history of childbirth and number of children. The results obtained from this study are that, the MOORA method can choose alternatives and rank when making recommendations for contraceptives that are suitable until they are as needed. Where the alternative pill (A5) is a contraceptive for couples of childbearing age that suits their needs. The highest Yi (Max) value is 0.2249